Sector growth and related index returns – an integration analysis of the group of seven - Mohamed,Taariq (College of Accounting, 2022)
This study examines the lagged short run and long-term relationships between output growth and related index returns of the industrial and financial sectors of the G-7 economies. This study examines this relationship using quarterly data for a maximum time period of 22 years ranging from 1994(Q4) to 2017(Q4). The relationship between sector specific output growth and related index returns of the G-7 is investigated within this study, in order to determine whether passive investors should incorporate expected growth prospects into their decision making in order to earn superior returns. In order to examine the relationship between sector specific output growth and the related index returns of the G-7, this study uses correlation, cointegration as well as causality testing. This study finds weak non-lagged correlation relationships between output growth and related index returns of the industrial and financial sectors of the G-7 economies, with the correlation relationships becoming stronger in all cases when lags are incorporated within the correlations analysis. This study also finds cointegrating relationships between financial sector output growth and related index returns of Italy and the United Kingdom and that financial index return data of the United Kingdom serves as a leading indicator for financial sector growth within the United Kingdom. The overall Implication of these results is that investors should not incorporate growth prospects into their decision making of which passive funds to invest in, of which these passive funds examined track the performance of industrial and the financial firms within the G-7 economies.